PENGARUH E-LEARNING DALAM PENGEMBANGAN TEKNOOGI INFORMASI PENDIDIKAN DI POLITEKNIK NEGERI SRIWIJAYA (REKAYASA DAN NON REKAYASA) - Afrizawati .; Paisal .; Yusuf . (JURNAL MANAJEMEN DAN BISNIS SRIWIJAYA, 2016)
The Purposed of this reseach to looked the influence of E-Learning in information techonology development at Polytechnic State of Sriwijaya (Engineering and non-Engineering). This reseach used primary data which is processing used multiple regression analysis with a sample drawn from the population of students on Polytechnic State of Sriwijaya. which has interacted directly with the research site. From the processing data in t test showed that the output reliability calculation analysis, known ralpha to variable Y at 0.8845, X1 0.8256 and X2 0.787. From the results of the Likert scale R value of 0.823 indicates that the correlation or relationship between E-learning with a variable development was very strong because it is on a scored of 0.80 to 1.00. Value Adjusted R Square or the coefficient of determination is 0.6.5. Simultaneous calculation based on the results obtained figures Fhitung 35.166> 2.7143. means that there are influence between the variables of planning, design and materials, delivery, interaction and Evaluation of E-Learning. So, it can be said that e-learning is one way in the development of information technology education in the State Polytechnic of Sriwijaya.